Demystification of the Myth of Freedom in the Characterization of Christopher McCandless in Krakauer's Into The Wild (NOBEL: Journal of Literature and Language Teaching, 2019)
While Krakauer's Into The Wild depicts McCandless' flee from society to live in the wild, many reviews argue that McCandless was not really a kind of person who finds freedom in nature. The present study will investigate further the surface characterizations of McCandless as freedom chaser with the plot development to fill the gap between McCandless' characterizations and the myth of freedom that he chases. By applying Barthes’ mythology, the study reveals that McCandless was described as an adventurer, immaterialist, and loner. However, the plot development reveals that as a person who sought an adventure in nature, McCandless would deal with water, but knowing that he had fear of water, it is contradictive with his characterization as an adventurer. As a person who rejected capitalism and materialist society, he was found working at McDonald's for having money in which both McDonalds and money are symbols of capitalism and materialistic society. As a person who spent his time mostly alone and intended to be alone in Alaska, he was a lonely person after all. Thus these contradictions demystify the myth of freedom that McCandless chases.